Targeting Cytoprotective Autophagy to Enhance Anticancer Therapies - Xiao, Malina; Benoit, Alice; Hasmim, Meriem; Duhem, Caroline; Vogin, Guillaume; Berchem, Guy; Noman, Muhammad Zaeem; Janji, Bassam (Frontiers in Oncology, 2021)
Autophagy is a highly regulated multi-step process that occurs at the basal level in almost all cells. Although the deregulation of the autophagy process has been described in several pathologies, the role of autophagy in cancer as a cytoprotective mechanism is currently well established and supported by experimental and clinical evidence. Our understanding of the molecular mechanism of the autophagy process has largely contributed to defining how we can harness this process to improve the benefit of cancer therapies. While the role of autophagy in tumor resistance to chemotherapy is extensively documented, emerging data point toward autophagy as a mechanism of cancer resistance to radiotherapy, targeted therapy, and immunotherapy. Therefore, manipulating autophagy has emerged as a promising strategy to overcome tumor resistance to various anti-cancer therapies, and autophagy modulators are currently evaluated in combination therapies in several clinical trials. In this review, we will summarize our current knowledge of the impact of genetically and pharmacologically modulating autophagy genes and proteins, involved in the different steps of the autophagy process, on the therapeutic benefit of various cancer therapies. We will also briefly discuss the challenges and limitations to developing potent and selective autophagy inhibitors that could be used in ongoing clinical trials.